2001
DOI: 10.1152/ajpheart.2001.281.4.h1545
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase isoforms and signal integration in models of vascular smooth muscle cells

Abstract: Adenylyl cyclases present a potential focal point for signal integration in vascular smooth muscle cells (VSMC) influencing contractile state and cellular responses to vessel wall injury. In the present study, we examined the influence of the vasoactive peptide arginine vasopressin (AVP) on cAMP regulation in primary cultures of rat aortic VSMC and in the A7r5 arterial smooth muscle cell line. In cultured VSMC and A7r5 cells, AVP had no effect on basal cAMP but differentially affected beta-adrenergic receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
4
26
0
3
Order By: Relevance
“…Previous data using heterologously expressed protein indicate that AC3 stimulation by Ca 2ϩ is dependent upon coincidental activation of AC by either G s or forskolin (18), results consistent with what we observe in cardiac fibroblasts. An important role for a Ca 2ϩ -stimulable AC isoform in the observed cross-talk is inferred by data from vascular smooth muscle (33) and directly supported by our studies overexpressing AC6. By increasing AC6 expression, we altered the balance of AC isoform expression in favor of an isoform not stimulated by Ca 2ϩ and found that the G q -G s cross-talk was fractionally reduced.…”
Section: Discussionsupporting
confidence: 80%
“…Previous data using heterologously expressed protein indicate that AC3 stimulation by Ca 2ϩ is dependent upon coincidental activation of AC by either G s or forskolin (18), results consistent with what we observe in cardiac fibroblasts. An important role for a Ca 2ϩ -stimulable AC isoform in the observed cross-talk is inferred by data from vascular smooth muscle (33) and directly supported by our studies overexpressing AC6. By increasing AC6 expression, we altered the balance of AC isoform expression in favor of an isoform not stimulated by Ca 2ϩ and found that the G q -G s cross-talk was fractionally reduced.…”
Section: Discussionsupporting
confidence: 80%
“…42,43 AVP treatment can amplify cAMP production when vascular smooth muscle cells are treated with a ␤-adrenoceptor agonist, although AVP alone does not elevate cAMP. 44 This effect is blocked by V 1a , but not V 2 antagonists, and appears to be dependent on the AVPinduced rise in [Ca 2ϩ ] i . 44,45 Some such signal cross-talk may explain the observations in our experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, relaxations to both agents were potentiated by inhibition of cAMP hydrolysis with IBMX. Although this phosphodiesterase inhibitor also unmasked a small concentration-dependent direct relaxant response to A-23187 in rings without endothelium, presumably by weakly stimulating the Ca 2ϩ -activated type VIII adenylyl cyclase isoform (31), submaximal relaxations of endothelium-intact rings to A-23187 were amplified by up to to threefold in the presence of IBMX. Responses to ACh and A-23187 were inhibited by the combination of apamin plus charybdotoxin, even when relaxation was potentiated by IBMX.…”
Section: Discussionmentioning
confidence: 95%